Study Of The Determinants Of Debt-Equity Choice In The Malaysian Corporate Sector - Sarada, L. (2008)
The present study is addressed to the identification of capital structure determinants in the Malaysian corporate sector. The extent of debt capital used differs from industry to industry and from company to company; moreover , the same company would be issuing debt capital sometimes and equity at other times. The objective of the present study is to identify the factors influencing leverage levels and debt/equity choices of the Malaysian Corporate Sector.